Punishment as moral communication: the experiences of long-term prisoners - Schinkel, Marguerite (Punishment & society, 2014)
This article examines for the first time to what extent the lived experience of long-term prisoners matches the normative theory of criminal punishment as moral communication. The findings are based on 27 narrative interviews with men at different stages of a long-term prison sentence. The analysis suggests that Antony Duff’s normative vision of punishment as moral communication may be difficult to realise in practice because of the inevitable pressures on defendants in the courtroom and on prisoners during their incarceration. In the court, the men’s attention was focused on the length of the sentence imposed; they were often overwhelmed by emotion and did not interact with the court as a moral arena. Within prison the men tended to accept their sentence in order to make bearing their incarceration easier. Comparing these men’s lived experiences of punishment with Duff’s normative theory highlights problems with the theory’s potential implementation but also reveals normative problems with current practices of sentencing and sanctionin